PENGARUH KUALITAS LAYANAN DAN PROMOSI TERHADAP MINAT MENJADI NASABAH BANK SYARIAH - Najibah, Rifdah; Kosim, Ahmad Mulyadi; Mulisin, Sofian (An Nuqud Journal of Islamic Economics, 2025)
This research is motivated by the interest of Islamic Bank customers which is an action of customers to choose and use services and products at the Islamic Bank. The purpose of this study was to determine the quality of service and promotion of interest in becoming customers. In this data collecting primary data with sample data collection techniques in the form of random sampling of one hundred seventy-three students of Ibn Khaldun University Bogor. Using a questionnaire with a Likert scale on students of Ibn Khaldun University Bogor. Instrument requirement testing used in this study includes validity uni, reliability test, normality test, multicollinearity test, heteroscedasticity test, t test (partial), f test (simultaneous), and determination coefficient test (R2). As testing requirements and hypothesis testing. The analysis technique used is multiple linear regression analysis. Based on the results of research using multiple regression analysis, it is obtained that service quality has an influence on interest in becoming customers and promotion also has an effect on interest in becoming customers. Service quality and promotion have a positive and significant effect both passively and simultaneously